Calibrating Student Perceptions of Punishment: a Specific Test of General Deterrence - Nixon, Timothy S. (American journal of criminal justice, 2019)
General deterrence theory assumes objective risks of punishment and citizens’ perceptions of punishment risks are closely calibrated. Yet little empirical attention has been devoted to testing this assumption. Of the few studies that exist, most have tested the calibration with county-level indicators of objective punishment risk. This strategy has been criticized for being too far removed from the individual citizen: why should we expect citizens to know the punishment risks in such a large geographic unit? We estimated the calibration between objective punishment levels and individuals’ perceptions of those punishment levels by analyzing data drawn from a large sample of students ( n = 11,085) from 44 schools in Ohio. Multi-level models found the calibration between objective punishment and students’ perceptions is weak and not statistically significant. More than half of our calibration estimates were in the wrong direction (i.e., they were negative) and results from interaction tests did not indicate that the calibration is any stronger among those with the highest levels of self-reported offending. We discuss the implications of these findings for policies rooted in general deterrence theory.